Design of a mini fatigue tensile machine - Khairol Naim Shafeei (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The project is about the design of mini fatigue tensile machine by designing a low cost for the use of students. The project aims to study the tensile that occurs to the specimen during the tensile process. The design of this machine will use UGNX 6.0 as the software machine design. This machine will make the process of repetition to get the fatigue tensile of the specimen.